2010
DOI: 10.1681/asn.2010030238
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Inhibits Renal Tubular Macroautophagy in Acute Kidney Injury

Abstract: Autophagy is a tightly regulated, programmed mechanism to eliminate damaged organelles and proteins from a cell to maintain homeostasis. Cisplatin, a chemotherapeutic agent, accumulates in the proximal tubules of the kidney and causes dose-dependent nephrotoxicity, which may involve autophagy. In the kidney, cisplatin induces the protective antioxidant heme oxygenase-1 (HO-1). In this study, we examined the relationship between autophagy and HO-1 during cisplatin-mediated acute kidney injury (AKI). In wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
125
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 50 publications
14
125
0
Order By: Relevance
“…It has previously been demonstrated that the overexpression of HO-1 reduces cisplatin-induced excessive autophagy in proximal tubule cells (3). In accordance with this previous finding, the current results further demonstrated that the pharmacological activation of HO-1 inhibits external oxidative stress-mediated autophagy in glomerular mesangial cells; however the inactivation of HO-1 exacerbates the autophagic response.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It has previously been demonstrated that the overexpression of HO-1 reduces cisplatin-induced excessive autophagy in proximal tubule cells (3). In accordance with this previous finding, the current results further demonstrated that the pharmacological activation of HO-1 inhibits external oxidative stress-mediated autophagy in glomerular mesangial cells; however the inactivation of HO-1 exacerbates the autophagic response.…”
Section: Discussionsupporting
confidence: 92%
“…Due to its beneficial effects, including oxidative stress relief and the inhibition of cell apoptosis, HO-1 has previously been proposed as a potential therapeutic target for ischemia/reperfusion or hypertension-induced glomerular injuries (2,3), and diabetic retinopathy (4). HO-1 has also been considered a potential biomarker of acute kidney injury (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Moreover, deletion of autophagy genes, including Atg5 and Atg7, blocks autophagy induction in AKI and enhances kidney injury. [66][67][68] It remains unclear as to how autophagy is activated in AKI. p53 inhibitors can partially suppress cisplatin-induced autophagy in renal tubular cells, 67 suggesting a role of p53 in triggering autophagy.…”
Section: Receptorsmentioning
confidence: 99%
“…Studies have indicated that upregulation of HMOX-1 is correlated with the inhibition of autophagy (19,20). Autophagy, which describes the process of cellular self-digestion, is considered to be a cytoprotective response, which may occur following the withdrawal of growth factors or under stressful conditions (21).…”
Section: Introductionmentioning
confidence: 99%